2018
DOI: 10.3390/nu10060767
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Mediterranean Diet and the Risk of Falls and Physical Function Indices in Older Type 2 Diabetic People Varies by Age

Abstract: Background and Aims: Diabetes and dysglycemia increase the risk of frailty and decreased physical abilities. Adherence to the Mediterranean Diet (MD) may reduce this risk. We hypothesized that adherence to the MD is associated with physical function in older type-2 diabetic patients and that the association is stratified by age. Methods and Results: We recruited type-2 diabetes patients aged >60 years at the Center for Successful Aging with Diabetes at Sheba Medical Center. Health status and demographic data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
3
23
0
2
Order By: Relevance
“…The mortality was lower in those with the healthy dietary pattern than in those with oily dietary pattern only among older patients aged over 75 years but not in those aged 65 to 74 years [180]. In addition, one study reported that patients with diabetes aged 75 years or older had improved walking and balance with improved adherence to the Mediterranean diet whereas a similar relationship was not observed in patients aged between 60 and 74 years [172]. Therefore, the dietary strategy of older people with diabetes should shift with advancing age from strict dietary restrictions for the treatment of MetS/obesity to diets for the prevention of frailty and sarcopenia.…”
Section: Age-related Differences In Nutritional Intake On Health Outcmentioning
confidence: 95%
See 2 more Smart Citations
“…The mortality was lower in those with the healthy dietary pattern than in those with oily dietary pattern only among older patients aged over 75 years but not in those aged 65 to 74 years [180]. In addition, one study reported that patients with diabetes aged 75 years or older had improved walking and balance with improved adherence to the Mediterranean diet whereas a similar relationship was not observed in patients aged between 60 and 74 years [172]. Therefore, the dietary strategy of older people with diabetes should shift with advancing age from strict dietary restrictions for the treatment of MetS/obesity to diets for the prevention of frailty and sarcopenia.…”
Section: Age-related Differences In Nutritional Intake On Health Outcmentioning
confidence: 95%
“…Meta-analyses of observational studies reveal that high adherence to the Mediterranean diet is associated with a significantly reduced risk of frailty and functional disability [170,171]. Although data are limited in patients with diabetes, some reports indicated that adherence to the Mediterranean diet was associated with decreases in both the prevalence [172] and incidence [173] of frailty in older patients. Moreover, a similar association was observed particularly in those aged over 75 years in a cross-sectional study [172].…”
Section: Mediterranean Diet and Healthy Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross-sectional analysis of 380 Spanish adults aged 55-80, higher adherence to a traditional Mediterranean dietary pattern was associated with greater walking distance on the 6MWT, while higher adherence to a Western dietary pattern was associated with a lower 6MWT distance [140]. In 117 individuals with T2DM, those over 75 years of age and in the highest tertile of adherence to the Mediterranean Diet demonstrated greater 6MWT and 10-min walk test distances than those less adherent [141].…”
Section: Dietary Patterns In Sarcopenia and Frailtymentioning
confidence: 97%
“…Em relação à prevenção de quedas em idosos frágeis, segundo Halfon, Phan e Teta (2015), a suplementação de vitamina D tem conduzido a uma redução desse risco sendo resultado de atuação direta nos músculos. Como também, é visto que o uso de dieta mediterrânea reduz o risco de quedas em pacientes idosos com Diabetes Mellitus tipo 2 (TEPPER et al, 2018) Atividades que aumentem a força muscular, equilíbrio e melhore a marcha podem diminuir a chances de a fragilidade resultar em quedas (CARORE et al, 2013), como também pode ser realizado Terapia Cognitiva Comportamental nos casos de idosos que apresentam medo de cair novamente, e com isso evitam realização de atividades do dia-a-dia, se isolando cada vez mais com consequência ocorrendo um aumento da fragilidade (PARRY et al, 2016) Por fim, Kojima (2015) e Perttila et al (2017) afirmam a existência da relação entre a Síndrome da Fragilidade e o evento de quedas em idosos, porém não elucidaram os fatores de riscos específicos para esse acontecimento.…”
Section: Discussionunclassified